Revisiting carotenoid aggregates discerning non-covalent interaction of unbranched fatty acid analogues - Simonyi, Miklós (Archives of Pharmacy and Pharmaceutical Sciences, 2022)
Certain carotenoid aggregates provide scaffolds of moderate stability characterized by their CD spectra. The interaction of the scaffold with small lipid molecules either destabilize, or reinforce its structure. The idea can be applied to open-chain fatty acids and some analogues. Fatty acids and fatty alcohol decrease exciton intensity of the aggregate, while esters of both alcohol and acids increase it. Moreover, the stabilizing effect depends on chain-length. Thus, the scaffold distinguishes compounds that either loosen its structure, or reinforce it.